The Relationships Between Danxia Geoheritages and Regional Tectonics in Southern Sichuan Basin: Implications for the Spatial Distribution of Danxia Landforms in China - Qiu, Jun-Ting; Mu, Hong-Xu; Rui, Xin-Min; Yang, Yan-Jie; Li, Pengju; Qiu, Liang; Xu, Chao-Bin (Geoheritage, 2024)
The Danxia geoheritage has emerged as a compelling subject of study, while the Tethys-Himalayan tectonic domain continues to captivate scholarly attention. However, a noteworthy gap exists in the literature concerning the intricate relationship between Danxia formation and the evolution of regional tectonics. In this study, we conducted a comprehensive analysis involving structure interpretation and terrain assessment, utilizing Landsat8 imagery and ASTER Global Digital Elevation Model. Additionally, field investigations were carried out on 35 Danxia landforms in the southern Sichuan Basin. Our findings revealed four distinct types of Danxia heritages—cliff (32 sites), peak (7 sites), cave (5 sites), and valley (6 sites)—with a predominant presence on slopes exceeding 40°. Moreover, valley-type sites exhibited a propensity for development at altitudes surpassing 400 m. The observed formations were intricately linked to Late Jurassic to Cretaceous red beds, influenced by the synergistic effects of the southward thrusting of the Qinling Orogen and the northwestward expansion of the Jiangnan Orogen. The control exerted by Cenozoic faults, folds, and joints—resulting from the eastward expansion of the Tibetan Plateau and the southeastward extrusion of the Chuandian terrane—further shaped these Danxia landscapes. Notably, the eastward expansion of the Tibetan Plateau induced the Cenozoic uplift of the southern Sichuan Basin, initiating a rapid denudation process of red beds crucial to the formation of Danxia landforms. Consequently, the Tethys-Himalayan tectonic evolution not only provided the material and structural foundations for these formations but also exerted a profound influence on their development in the southern Sichuan Basin. This study significantly contributes to our enhanced understanding of the spatial distribution of Danxia landforms in China.